Negotiation of Muslim Worship during the Pandemic Covid-19: Lessons Learned for Post-Pandemic - Henky Fernando; Irwan Abdullah; Mohamad Yusuf (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
The negotiation of Muslim worship during the pandemic Covid-19 is very important to reflect on as a lesson learned after the pandemic Covid-19. This study, in addition to provide a conceptual understanding of the pattern of negotiating Muslim worship during the pandemic Covid-19, reflected this negotiation contextually. This study used a qualitative approach. Data collection was carried out through an interview with Muslims who actively carried out worship activities in the congregation during the pandemic Covid-19 at the Kotagede Mataram Gede Mosque. The analysis was carried out through the process of reducing, describing, and inductively interpreting data to obtain a classification and conclusion regarding the pattern of negotiating Muslim worship during the pandemic Covid-19. This study found that the pattern of negotiating Muslim worship during the pandemic Covid-19 was not least carried out through three contexts, namely, a negotiation in a structural context, a negotiation in a cultural context, and a negotiation in a spiritual context. These three contexts were an effort of Muslim resilience in accommodating their worship activities during the pandemic Covid-19.